Placebo‐controlled study on the effects of oral administration of Allium sativum L in postweaning piglets. (9th March 2019) - Ayrle, Hannah; Nathues, Heiko; Bieber, Anna; Durrer, Manuela; Quander, Nele; Mevissen, Meike; Walkenhorst, Michael
Abstract : Postweaning diarrhoea (PWD) due to Escherichia coli is an economically important disease in pig production. In this placebo‐controlled study performed in Switzerland, the effects of oral supplementation of Allium sativum L. (garlic, AS) on performance (bodyweight (BW) and daily weight gain (DWG)) and health (body condition and clinical score) were investigated in postweaning piglets. Piglets (n=600) were randomly assigned to the treatment groups (placebo, AS or colistin) and observed from birth until three weeks postweaning. The treatments were administered for the first two weeks postweaning. Faecal dry matter (FDM) and coliform bacteria on pen level were measured weekly. Data were analysed using generalised mixed‐effect models in R. BW and DWG of the AS group were significantly higher compared with placebo in the third week postweaning. No differences in body condition and FDM were observed. The clinical score of AS‐treated animals was significantly better compared with the colistin group. About 33 per cent of the piglets of the AS and the placebo group had to be treated with antibiotics due to the occurrence of severe PWD. The major finding of this study showed that AS supplementation increased growth performance and improved clinical health, but did not reduce the incidence and severity of PWD.